Systematic Analysis and Validation of the Prognosis, Immunological Role and Biology Function of the Ferroptosis-Related lncRNA GSEC/miRNA-101-3p/CISD1 Axis in Lung Adenocarcinoma - Jiang, Xiulin; Yuan, Yixiao; Tang, Lin; Wang, Juan; Zhang, Dahang; Duan, Lincan (Frontiers in Molecular Biosciences, 2022)
Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for approximately 85% of lung cancers. Emerging evidences demonstrated that ferroptosis plays a central role in immune responses as well as tumor cell proliferation. However, the clinical significance, immunological function and possible upstream modulate mechanism of ferroptosis‑related genes in NSCLC remains unclear. In this research, we using various bioinformatics identified differentially expressed and prognosis-related ferroptosis genes in NSCLC, and using these DEGs constructed a prognostic ferroptosis-related genes (FRGs) as well as related ceRNA modulates network. Furthermore, we utilized pearson’s correlation evaluated the correlation between FRGs and TMB, MSI, tumour-immune infiltration, immune checkpoints as well as diverse drug sensitivity in NSCLC. We conducted loss of function to verify the function of CISD1 in NSCLC progression. We uncover that FRGs (CISD1, ATP5MC3, PGD, SLC7A11, ACSL3 and FANCD2) was significantly up-regulated in NSCLC and elevated expression of FRGs was associated with pathologic stage and unfavorable prognosis. Furthermore, KEGG enrichment results demonstrated that these FRGs mainly involve in the ferroptosis and glutathione metabolism in NSCLC. More importantly, we using six prognostic related genes construction a prognostic FRGs model that could be predict the overall survival of NSCLC patients possess high specificity and accuracy. Finally, we uncover that FRGs significantly correlated with the TMB, MSI, immune-cell infiltration, immune checkpoint as well as diverse cancer related drug sensitivity. Additionally, we identified the upstream regulatory axis of FRGs (CISD1, ATP5MC3, PGD) in NSCLC, namely lncRNA GSEC/miRNA-101-3p axis. We uncover that GSEC, CISD1, ATP5MC3 and PGD were up-regulated or miRNA-101-3p was down-regulated in NSCLC, respectively. IHC assay demonstrated that CISD1, ATP5MC3 and PGD were overexpressed in NSCLC tissue. Knock down of CISD1 significantly inhibits NSCLC cell proliferation and migration abilities. In summary, this is the first study to characterize the functional roles of lncRNA GSEC/miR-101-3p/ FRGs axis in NSCLC, which provides potential diagnostic and therapeutic biomarkers for NSCLC in the future.